PENGEMBANGAN PERMAINAN MONOPOLI BERBASIS PAPAN ILMU PENGETAHUAN MATA PELAJARAN IPS PADA SISWA KELAS V DI SDN 101751 DESA KLAMBIR LIMA KECAMATAN HAMPARAN PERAK, KAB. DELI SERDANG SUMATERA UTARA - Aditya Nugraha; Solihah Titin Sumanti; Abdul Gani Jamora Nasution (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This study aims to develop and implement a science board-based monopoly game in Social Sciences (IPS) subjects for 5th grade elementary school students. This monopoly game is designed as an innovative learning media that can increase learning interest, active involvement in students, increase learning motivation, active participation, and student understanding of IPS material. This study uses the Research and Development (R&D) method and with the 4D development model, namely Define, Design, Develop, and Disseminate which involves the stages of needs analysis, product design, expert validation, product trials, and evaluation. The results of the study showed that: 1) Based on the results of the average feasibility of the expert material validator assessment, media experts and teacher responses showed that the media for developing a monopoly game based on the IPS science board that had been developed with an average percentage value of 94.625% so that it was included in the category of feasible to use. 2) Based on the average results of the practicality of a media, students gave a very positive response to the media for developing monopoly games based on the social studies subject science board that was developed, showing the overall percentage results obtained from the distribution of student response questionnaires for class V SDN 101751 Klambir V, Hamparan Perak District, Deli Serdang Regency with an average value of 90% with a very practical category. 3) Based on the results of the average effectiveness of the Pretest and Post-test through a Likert scale, it shows that the media for developing monopoly games based on the social studies subject science board that has been developed is included in the Effective category, with an average percentage value of 90.68%. n So it can be concluded that the media for developing monopoly games based on the social studies subject science board for class V students at SDN 101751 Klambir Lima Village, Hamparan Perak District, Deli Serdang Regency, North Sumatra is very effective so that it is suitable for use in the learning process.